2022
DOI: 10.3390/biomedicines11010063
|View full text |Cite
|
Sign up to set email alerts
|

FDG PET Imaging of the Pain Matrix in Neuropathic Pain Model Rats

Abstract: Pain is an unpleasant subjective experience that is usually modified by complex multidimensional neuropsychological processes. Increasing numbers of neuroimaging studies in humans have characterized the hierarchical brain areas forming a pain matrix, which is involved in the different dimensions of pain components. Although mechanistic investigations have been performed extensively in rodents, the homologous brain regions involved in the multidimensional pain components have not been fully understood in the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Increased tracer uptake in the lumbar spinal canal in the rat model of pain was observed. The elevated [ 51 Mn] Mn 2þ uptake can be observed after six days post-complete Freund's adjuvant, and the highest signal was found on day one post-injection [75].…”
Section: [ 51 Mn]mn 2þmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased tracer uptake in the lumbar spinal canal in the rat model of pain was observed. The elevated [ 51 Mn] Mn 2þ uptake can be observed after six days post-complete Freund's adjuvant, and the highest signal was found on day one post-injection [75].…”
Section: [ 51 Mn]mn 2þmentioning
confidence: 99%
“…Imaging data showed increased [ 18 F]FDG uptake in the medial prefrontal cortex, primary somatosensory cortex hindlimb region, and the centrolateral thalamic nucleus. The increased [ 18 F]FDG uptake was positively correlated with von Frey test data [51].…”
Section: Pet Tracers For Pain Imaging and Imaging Findingsmentioning
confidence: 99%
“…For example, research on neuropathic pain has demonstrated altered glucose metabolism in specific brain regions, such as the thalamus, insula, and anterior cingulate cortex, which are involved in pain perception and modulation. 27 Moreover, [18F]-FDG-PET has shown promise in identifying biomarkers for pain severity and treatment response in chronic pain patients, offering a potential means for personalized pain management. 28 A study by Biswal and colleagues evaluated [18F]-FDG imaging in six patients with chronic neuropathic pain in their lower extremities (four cases of complex regional pain syndrome, one case of chronic sciatica, and one case of neuropathic pain).…”
Section: [18f]-fluorodeoxyglucosementioning
confidence: 99%
“…For example, research on neuropathic pain has demonstrated altered glucose metabolism in specific brain regions, such as the thalamus, insula, and anterior cingulate cortex, which are involved in pain perception and modulation. 27 Moreover, [18F]-FDG-PET has shown promise in identifying biomarkers for pain severity and treatment response in chronic pain patients, offering a potential means for personalized pain management. 28…”
Section: Reviewmentioning
confidence: 99%
“…Recently, brain activity in regions such as the medial prefrontal cortex, primary somatosensory cortex hindlimb region, and the centrolateral thalamic nucleus were shown to be positively correlated with mechanical allodynia-related behavioral changes. 86 Behera et al used PET/MRI in a rat model to pinpoint increased 18F-FDG uptake in damaged nerves. The absorption of 18F-FDG and behavioral tests for allodynia in the afflicted paw were highly linked.…”
Section: Molecular Imaging For Chronic Painmentioning
confidence: 99%